Efisiensi Kinerja Lembaga Amil Zakat Dalam Mengelola Dana Dengan Metode DEA (Studi Pada Yayasan Dana Sosial al-Falah Surabaya) (UIN Sunan Kudus, 2019)
Efficiency is a parameter to measure the performance of companies and organizations. As an institution in charge of managing the funds of the people, this institution need for special attention, it use to see the professionalism of these institutions manage ZIS fund. This study aims to determine the efficiency of the management of zakat, donation and sadaqah (ZIS) at amil zakat Yayasan Dana Sosial Al - Falah (YDSF) Surabaya by using descriptive quantitative approach. The technique of collecting data in the form of documentation and interviews, using secondary data in the form of financial statements institute period 2015 - 2017. The data analysis technique uses data envelopment analysis (DEA) with the production approach, the orientation of the input and output. Input variables include total assets and operating costs, while the output variable includes the amount of ZIS funds collected and distributed, using the assumption of a variable return to scale (VRS). The results showed that the production approach Yayasan Dana Sosial Al - Falah (YDSF) had maximum efficiency with a value of 100 percent or 1, in the period 2015, 2016 and 2017. Based on these results mean Yayasan Dana Sosial Al - Falah (YDSF) has reached optimal performance in managing ZIS, it proved by using input and output which is in accordance with the actual value and the target at the measurement Data envelopment analysis (DEA).